RANCANG BANGUN SISTEM INFORMASI AKADEMIK FMIPA UNIVERSITAS TADULAKO BERBASIS ANDROID - Prasetyo, W F; Sudarsana, I W; Lusiyanti, D (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Academic information system based on Android necessary to support the effectiveness management of academic data such as input card study plan and input the value of course. To build Siakad Android application, the authors do the research of the database web Siakad Faculty of Natural Science Tadulako University that includes all the data of students, faculty, courses, card study plan, and card study result. The purpose of this study was to obtain academic information system based on Android Tadulako University Faculty of Mathematics and Natural Sciences. This application is built with features such as view bio, view the result of study, view the transcript, input study plan card, input result study card, wait confirm of study plan, and confirm study plan. Based on the results and discussion, it can be concluded that academic information system can support the effectiveness of academic data processing, such as the study plan input, and the input value of the course.